2021
DOI: 10.3390/molecules26165046
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of NiFe-Layered Double Hydroxide and Mixed Metal Oxide with Excellent Microwave Absorption Properties

Abstract: Microwave-absorbing materials have attracted increased research interest in recent years because of their core roles in the fields of electromagnetic (EM) pollution precaution and information security. In this paper, microwave-absorbing material NiFe-layered double hydroxide (NiFe-LDH) was synthesized by a simple co-precipitation method and calcined for the fabrication of NiFe-mixed metal oxide (NiFe-MMO). The phase structure and micromorphology of the NiFe-LDH and NiFe-MMO were analyzed, and their microwave-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…42 Significant fluctuations can be seen at high frequencies (14–18 GHz) because the polarization is largely influenced by the frequency, and the electron exchange between Fe 3+ and Ni 2+ ions in MNFM and the special heterogeneous structure induced by the alternating electric field lead to a large amount of space and polarization charges, resulting in small fluctuations at high frequencies. 43 From Fig. 5(a and b), the permittivity of MNFM is higher than that of NFM, and the ε ′ value of MNFM is greater than that of NFM, which can be explained by the incorporation of MnO 2 , which gives MNFM a better impedance match and provides MNFM with a multilayer structure and nano-sheet layers that provide more incidence and storage channels for electromagnetic waves.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…42 Significant fluctuations can be seen at high frequencies (14–18 GHz) because the polarization is largely influenced by the frequency, and the electron exchange between Fe 3+ and Ni 2+ ions in MNFM and the special heterogeneous structure induced by the alternating electric field lead to a large amount of space and polarization charges, resulting in small fluctuations at high frequencies. 43 From Fig. 5(a and b), the permittivity of MNFM is higher than that of NFM, and the ε ′ value of MNFM is greater than that of NFM, which can be explained by the incorporation of MnO 2 , which gives MNFM a better impedance match and provides MNFM with a multilayer structure and nano-sheet layers that provide more incidence and storage channels for electromagnetic waves.…”
Section: Resultsmentioning
confidence: 91%
“…It was demonstrated that the domain wall resonance occurs within a very small band of frequencies, so the domain wall displacement loss is not considered. 43 Its eddy current loss is described as follows: C o = μ ′′( μ ′) −2 f −1 = 2π μ o d 2 δ . 45 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistive absorbing materials such as carbon materials have the advantages of high conductivity loss, low density and abundant dipoles, but they have poor impedance matching characteristics and high reflectivity; thus, it is difficult for electromagnetic waves to incident into the material, and a large number of electromagnetic waves are reflected into space, resulting in secondary pollution [9,10]. Magnetic metal wave-absorbing materials have excellent properties, such as high dielectric constant and permeability, high magnetic loss, high cut-off frequency, high saturation magnetization strength, and good temperature stability, which are a class of wave-absorbing materials with great development potential and application prospects [11][12][13]. Among them, Fe magnetic metal has the best performance, the most research, and the most extensive application.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Although singlecomponent EMW absorption materials with satisfactory EMW absorption performance to some degrees have been reported, their disadvantages such as large filler content, high density, and narrow effective absorption bandwidth extremely limit their practical applications. 8,9 Consequently, recent studies focused on the rational incorporation of the dielectric component and magnetic component with an ingenious structure to realize high-performance EMW absorption. 10 Many typical biomass-derived carbon-based porous materials, such as wheat straw, pomelo peel, and wood, have attracted tremendous attention to fabricate efficient EMW absorption materials with a low filler content, low density, and broad effective absorption bandwidth because they can provide abundant inherent microscale pores for scattering and multiple reflections of electromagnetic waves.…”
Section: Introductionmentioning
confidence: 99%